Advanced Imaging of Gout and Other Inflammatory Diseases Around the Knee - Sudoł-Szopińska, Iwona; Lanckoroński, Michał; Teh, James; Diekhoff, Torsten; Giraudo, Chiara; Chaudhary, Snehansh Roy (Seminars in Musculoskeletal Radiology, 2024)
The knee is one of the most commonly affected joints in the course of inflammatory arthropathies, such as crystal-induced and autoimmune inflammatory arthritis. The latter group includes systemic connective tissue diseases and spondyloarthropathies. The different pathogenesis of these entities results in their varied radiologic images. Some lead quickly to joint destruction, others only after many years, and in the remaining, destruction will not be a distinguishing radiologic feature.Radiography, ultrasonography, and magnetic resonance imaging have traditionally been the primary modalities in the diagnosis of noninflammatory and inflammatory arthropathies. In the case of crystallopathies, dual-energy computed tomography has been introduced. Hybrid techniques also offer new diagnostic opportunities. In this article, we discuss the pathologic findings and imaging correlations for crystallopathies and inflammatory diseases of the knee, with an emphasis on recent advances in their imaging diagnosis.
Keywords: knee; imaging; gout; rheumatoid arthritis; spondyloarthropathy